IDNLearn.com is committed to providing high-quality answers to your questions. Our experts are ready to provide prompt and detailed answers to any questions you may have.
Sagot :
To factorize the polynomial [tex]\( 4x^2 + 23x - 72 \)[/tex], we need to identify the correct factored form among the given options.
Let's examine each option to determine which one properly reconstitutes the given polynomial when expanded:
1. [tex]\((4x + 8)(x - 9)\)[/tex]:
[tex]\[ (4x + 8)(x - 9) = 4x \cdot x + 4x \cdot (-9) + 8 \cdot x + 8 \cdot (-9) \\ = 4x^2 - 36x + 8x - 72 \\ = 4x^2 - 28x - 72 \][/tex]
This does not match [tex]\(4x^2 + 23x - 72\)[/tex].
2. [tex]\((4x - 8)(x + 9)\)[/tex]:
[tex]\[ (4x - 8)(x + 9) = 4x \cdot x + 4x \cdot 9 + (-8) \cdot x + (-8) \cdot 9 \\ = 4x^2 + 36x - 8x - 72 \\ = 4x^2 + 28x - 72 \][/tex]
This does not match [tex]\(4x^2 + 23x - 72\)[/tex].
3. [tex]\((4x + 9)(x - 8)\)[/tex]:
[tex]\[ (4x + 9)(x - 8) = 4x \cdot x + 4x \cdot (-8) + 9 \cdot x + 9 \cdot (-8) \\ = 4x^2 - 32x + 9x - 72 \\ = 4x^2 - 23x - 72 \][/tex]
This does not match [tex]\(4x^2 + 23x - 72\)[/tex].
4. [tex]\((4x - 9)(x + 8)\)[/tex]:
[tex]\[ (4x - 9)(x + 8) = 4x \cdot x + 4x \cdot 8 + (-9) \cdot x + (-9) \cdot 8 \\ = 4x^2 + 32x - 9x - 72 \\ = 4x^2 + 23x - 72 \][/tex]
This matches [tex]\(4x^2 + 23x - 72\)[/tex].
Therefore, the factored form of the polynomial [tex]\( 4x^2 + 23x - 72 \)[/tex] is [tex]\((4x - 9)(x + 8)\)[/tex]. Thus, it matches the fourth option provided in the question.
Let's examine each option to determine which one properly reconstitutes the given polynomial when expanded:
1. [tex]\((4x + 8)(x - 9)\)[/tex]:
[tex]\[ (4x + 8)(x - 9) = 4x \cdot x + 4x \cdot (-9) + 8 \cdot x + 8 \cdot (-9) \\ = 4x^2 - 36x + 8x - 72 \\ = 4x^2 - 28x - 72 \][/tex]
This does not match [tex]\(4x^2 + 23x - 72\)[/tex].
2. [tex]\((4x - 8)(x + 9)\)[/tex]:
[tex]\[ (4x - 8)(x + 9) = 4x \cdot x + 4x \cdot 9 + (-8) \cdot x + (-8) \cdot 9 \\ = 4x^2 + 36x - 8x - 72 \\ = 4x^2 + 28x - 72 \][/tex]
This does not match [tex]\(4x^2 + 23x - 72\)[/tex].
3. [tex]\((4x + 9)(x - 8)\)[/tex]:
[tex]\[ (4x + 9)(x - 8) = 4x \cdot x + 4x \cdot (-8) + 9 \cdot x + 9 \cdot (-8) \\ = 4x^2 - 32x + 9x - 72 \\ = 4x^2 - 23x - 72 \][/tex]
This does not match [tex]\(4x^2 + 23x - 72\)[/tex].
4. [tex]\((4x - 9)(x + 8)\)[/tex]:
[tex]\[ (4x - 9)(x + 8) = 4x \cdot x + 4x \cdot 8 + (-9) \cdot x + (-9) \cdot 8 \\ = 4x^2 + 32x - 9x - 72 \\ = 4x^2 + 23x - 72 \][/tex]
This matches [tex]\(4x^2 + 23x - 72\)[/tex].
Therefore, the factored form of the polynomial [tex]\( 4x^2 + 23x - 72 \)[/tex] is [tex]\((4x - 9)(x + 8)\)[/tex]. Thus, it matches the fourth option provided in the question.
We appreciate your participation in this forum. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. IDNLearn.com is committed to your satisfaction. Thank you for visiting, and see you next time for more helpful answers.